Teachers’ Interests and Competencies in Doing Research: Sequential Exploratory Analysis in Elementary School Teacher - Kurniawan, Dwi Agus; Syahrial, Syahrial; Perdana, Rahmat; Ikhlas, Muhammad; Kuswanto, Kuswanto (FKIP Universitas Lampung, 2020)
Teachers’ Interests and Competencies in Doing Research: Sequential Exploratory Analysis in Elementary School Teacher. Objectives: This study aims to look at teacher research competencies, teacher’s interest in conducting research, and the influence of that teacher’s interest toward teacher research competencies. Methods: This research is mixed research with a sequential explanatory approach, which Quantitative data followed by qualitative data. The sample in this study amounted to 129 teachers, which were obtained with a multi-stage sampling technique. Findings: The results show that the teacher’s research competence and interest in researching were categorized as fair or still lacking. Further analysis showed that the teacher’s interest influenced teacher research competence by 52.2%. Furthermore, the interview results show that some teachers have problems in doing research, such as lack of literature access, and lack of understanding of how to do research. Conclusion: Thus, it can be concluded that the research competence of teachers and the interest of teachers in researching is still relatively low.Keywords: teachers’ interest and competencies, elementary school teachers, factor analysis.DOI: 10.23960/jpp.v10.i2.202006